The Relationship Between Knowledge Level and Premarital Sexual Behavior Among Students of SMA PGRI 10 Glenmore - Maya Lutfiana Ningrum; Tria eni; Septi Kurniawati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction : Adolescence is a phase where individuals experience emotional, psychosocial development and move towards a certain maturity. According to Media Sains Indonesia (2022), the consequences of premarital sexual relations, such as pregnancy at a young age, can bring physical, psychological and social risks for teenagers, including the possibility of abortion. Objectives: Research shows that 86% of students have held hands and hugged their partners, with 20% of these activities done voluntarily, and 34% engaging in sexual activities every time they meet. As many as 42% of respondents revealed that the most common places to engage in sexual activities are in boarding houses or hotels. Methods : Research design is a framework that provides clear guidance and direction for researchers during the conduct of research. The aim is to provide detailed instructions so that researchers can follow the research stages correctly. This research uses a descriptive quantitative approach with a design that includes observational analysis and applies a cross sectional approach. Results : The research results show that there is no relationship between the level of knowledge regarding premarital sexual behavior among students and female students at SMA PGRI 10 Glenmore. This result can be seen from the p value of 0.848, so (H0) in this study is accepted. Thus it can be concluded that the level of knowledge has no relationship with premarital sexual behavior. Conclusions : Analysis shows that out of 60 respondents with good knowledge, 5 respondents (8.2%) have a positive risk towards premarital sexual behavior, while 34 respondents (55.7%) have a negative risk. On the other hand, out of 10 respondents (16.4%) with less knowledge, 9 respondents (14.8%) showed a negative risk and 1 respondent (1.6%) showed a positive risk towards premarital sexual behavior. The statistical test using chi-square yielded a significant value of ρ = 0.848. Because the ρ-value is greater than 0.05, it can be concluded that there is no relationship between the level of knowledge and premarital sexual behavior.